Improving the quality of life of the elderly through a healthy and active lifestyle in Kepandean Village, Tegal District - Andari, Istiqomah Dwi; Chikmah, Adevia Maulidya; Harnawati, Riska Arsita (Journal of Community Service and Empowerment, 2024)
A healthy concept encompasses various aspects of a person's life, including physical health, mental well-being, social relationships, and satisfaction with overall living conditions. For seniors, improving quality of life means ensuring that they can live fulfilling and meaningful lives in their senior years. Improving the quality of life of the elderly means paying attention to their needs holistically and providing appropriate support in various aspects of life. This article describes a program where participants will be given socialization on exercise practices and health checks for the elderly to improve the quality of life of the elderly seen from a healthy and active lifestyle. The aim of this service activity is to improve the welfare and quality of life of the elderly by providing information to the elderly about the importance of implementing lifestyle live a healthy and active life. Carrying out regular health checks can provide aspects in detecting health problems that may require immediate treatment. The service activity program includes various steps, including an initial test to measure the initial knowledge of the elderly, and a post-service evaluation to assess knowledge retention and health monitoring for the elderly. The results show a significant increase in knowledge and activity results after group exercise activities carried out by the elderly.